Twins with hereditary sensory and autonomic neuropathy type IV with preserved periodontal sensation - Yeliz Guven (2018)
Turkish twin brothers affected with hereditary sensory and autonomic neuropathy type IV (HSAN IV) are reported. Their clinical findings were generally typical for HSAN IV. Interestingly they both had preserved periodontal sensation. Mutation analysis of the NTRK1 gene showed a homozygous c.2001C > T substitution in exon 15 in both twins. This base substitution is predicted to change a polar, positively charged amino acid arginine to the highly active amino acid cystein at position 654 (p.Arg654Cys). The parents were heterozygous for the mutation. This mutation has been reported previously in one Japanese and one Arab patients. The preserved periodontal sensation has not previously been reported in patients affected with HSAN IV. This preserved sensation in our patients might have been through Ruffini endings, the periodontal mechanoreceptors which have been reported to be present in TrkA knockout mice. Here we report the first twins affected with HSAN IV and the observation that periodontal sensation is not affected by mutation in NTRK1. © 2014 Elsevier Masson SAS.